LAW ENFORCEMENT ON CAMPAIGN ACTIVITIES IN PLACES OF WORSHIP CASE STUDY OF DECISION NUMBER 56/PID.SUS/2019/PN SKH - Filadelfia Langit Ayu Sukmadila; Lusia Indrastuti; Esti Aryani (Wacana Hukum, 2021)
This study aims to find out the basis of Law Enforcement on campaign activities in places of worship that focuses on the Sukoharjo District Court Decision Number 56/Pid.Sus/2019/PN Skh, a case related to this research regarding campaign activities in places of worship.One of the characteristics of a democratic country is the existence of people's sovereignty within the country, and Indonesia is a country that adheres to the Pancasila Democracy system, as evidenced by the holding of General Elections, hereinafter referred to as General Elections. The implementation of elections is regulated in Law No. 7 of 2017 concerning General Elections, which also regulates election crimes, the legal basis is formed and enforced to maintain the dignity of democracy that applies in Indonesia.This research method in writing this thesis uses a normative type of research, which is carried out by reviewing secondary data, which includes primary legal materials, secondary legal materials, and tertiary legal materials. The nature of the research is descriptive, which is to describe the basis of the prosecutor's considerations in giving demands and the judge's considerations in making decisions as well. The duty of a Prosecutor as a Public Prosecutor is to prove his indictment. Where the decisions and demands of judges and prosecutors must uphold the value of justice, and not forget the value of humanity. As well as the judge's consideration in deciding this case, seeing from the indictment that the indictment was prepared on a subsidiary basis, it became the authority of the Panel of Judges to prove the indictment of Article 521 Jo. Article 280 paragraph (1) letter h of Law No. 7 of 2017 concerning General Elections.also pay attention to non-juridical elements.